Consuming Beauty in the Weimar Republic: A Discussion of Youth, Cosmetics, and Power in Vicki Baum's play Pariser Platz 13 (1930) - Victoria Vygodskaia - Rust (Studies in 20th & 21st Century Literature, 2019)
Published in 1930, Vicki Baum’s play Pariser Platz 13: Eine Komödie aus dem Schönheitssalon engaged the readership with an unorthodox and thoroughly modern heroine: the successful owner of international beauty salons Helen Bross. Helen personified the wishes and dreams of Baum’s readers: Helen’s autonomy, both personal and financial, allowed her to be an active consumer of modernity and its pleasures: travel, interaction with celebrities, and luxurious lodging. My paper studies a (fictional) beauty salon on Pariser Platz in Berlin as an enclave of female power and explores Vicki Baum’s portrayal of beauty, youth, and fashion as commodities. I place my reading of Pariser Platz 13 into the context of Baum’s own career; the Weimar Republic’s national and ethnic identities and its social and economic tensions, focusing on the role that the Austrian-Jewish author herself and her female heroines played as producers, transmitters, and consumers of contemporary beauty ideals. While looking at Baum’s heroines, I examine their possible historical prototypes, the cosmetics gurus Helena Rubenstein and Elizabeth Arden, analyzing the impact that their marketing strategies may have had on Baum and her readership. In addition to Pariser Platz 13, I delve into Baum’s novel Der Große Ausverkauf (A Big Sale 1937), written seven years later in the USA, in which the protagonists participate in conspicuous consumption at a New York department store, both as agents and objects. I argue that the department store and beauty salon embody quintessential metaphors for the experience of modern life in the 1920s and the 1930s. On the one hand, these sites provided opportunities for the construction of a modern female identity; on the other, they exposed the limits of female agency and disclosed how popular press and cosmetics advertisements disseminated the cultural icon of the new woman.
Keywords: New Woman; beauty salon; Vicki Baum; cosmetics; department store; Weimar Republic